Trabalho docente: um estudo sobre a mediação na prática de professoras de ciências naturais - Fornazari, Glaucia (2004)
This dissertation is the result of a research which took place in a public school in the city of São Paulo. Our object was the investigation into the work of two teachers of Natural Sciences, from the planning to the practice in the third grade classes of the second Cycle of the Ensino Fundamental (equivalent to the elementary school in the United States). The aim was to comprehend the relationship between the teachers and the development of their work, their relationship with Science and with their students. There was an ethnographic research that showed that in every stage the work of the teachers Maria and Vilma was disconnected from political and social interests. As historical beings, capable of transforming nature, social relationships and thoughts, they did not establish teleological positions. As a consequence, they did not create the ideal conditions for strengthening their and their students freedom; on the contrary, all the actions contributed to making the relationships of domination stronger.